Latin American Development and Public Policy
XVI, 317 p.
Keywords: This book analyzes various important aspects of methodology and substance regarding economic, social, and political policy in Latin America directed toward achieving more effective, efficient, and equitable societal institutions. The chapters are authored by experts from within Latin America and also from Latin America research institutes elsewhere. The book combines practical policy significance with insightful causal and prescriptive generalizations. The emphasis is on the role of governmental decision-making and the important (but secondary) role of the marketplace, social groups, and engineering.